Code-Switching and Portuguese Influence in the Invention of Tetun-Portu as a Creole - Ma'u, Jean Antunes Rudolf Zico (Indonesian Journal of English Language Studies (IJELS), 2019)
A creole is a pidgin that has attained the first generation of the speaker. The formation of a creole might be influenced by several factors and the two of them are code-switching and the influence of a dominant language. In relation to the two factors, there is a creole that might fit the situation. The creole is the Tetun-Portu language and the creole is presumably invented from the combination between the Tetun-Terik language and the Portuguese language. The backbone of the language might be adopted from the Tetun-Terik language but the codes have been dominated by the Portuguese language. The invention of the creole might be related to the Portuguese occupation in the Timor Island several centuries ago. Due to the interesting characteristics, the researcher would like to investigate the creole further. In conducting the study, the focus will be on how the code-switching influence the invention of the creole and the Portuguese influence within the invention of the creole itself. The findings of the study confirm that the Tetun-Portu language might be considered as a creole because it has completely different structures and it has adopted more codes from the Portuguese language.Keywords: Creole, Tetun-Terik, Tetun-Portu, code-switching, Portuguese influence